Differential mortality from external causes in Brazil from 2000 to 2022 - Aurelia Herminia Castiglioni (Geografares, 2024)
External causes constitute a heterogeneous set, comprising components with distinct determinants, profiles, and trends. This study aims to analyze the sociodemographic characteristics, trends, and spatial distribution of mortality from external causes and its main components in Brazil and its Federative Units from 2000 to 2022. The methodology involves the construction of indicators, the application of methods to assess trends, and the spatial represent. Mortality from external causes ranks fourth among all causes of death. Its main components —homicides, transport accidents, falls, and self-inflicted injuries—exhibit diverse trends. Falls increased by 322.95% over the period; suicides, by 142.80%; transport accidents, by 17.70%; whereas homicides registered a decrease of 2.19%. Given its magnitude and consequences for individuals, families, and society, mortality from external causes represents a significant challenge for public health and policy programs aimed at preventing and reducing these avoidable harms.
Keywords: external causes; socio-demographic characteristics; spatiotemporal analysis; Brazil